2022
DOI: 10.3389/fmicb.2022.859420
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of Influenza A NS1 and Cellular TRBP Protein Modulates the Function of RNA Interference Machinery

Abstract: Influenza A virus (IAV), one of the most prevalent respiratory diseases, causes pandemics around the world. The multifunctional non-structural protein 1 (NS1) of IAV is a viral antagonist that suppresses host antiviral response. However, the mechanism by which NS1 modulates the RNA interference (RNAi) pathway remains unclear. Here, we identified interactions between NS1 proteins of Influenza A/PR8/34 (H1N1; IAV-PR8) and Influenza A/WSN/1/33 (H1N1; IAV-WSN) and Dicer’s cofactor TAR-RNA binding protein (TRBP). W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 78 publications
0
1
0
Order By: Relevance
“…It also indicates that VSRs in insect cells share characteristics similar to those found in plant or animal cells, such as the P19 protein’s ability to bind with newly formed 21 nt and 22 nt RNA in plant cells, thereby hindering RISC assembly [ 26 , 44 ]. This regulatory mechanism is not limited to single-stranded RNA viruses but is also observed with FHV-B2 protein, NS1 protein of influenza A virus, Tomato aspermy virus (TAV)-2b protein, and other similar proteins [ 45 , 46 , 47 ]. Despite changes in gene regulation, there was no significant alteration observed within 24 h regarding the rate of apoptosis in Sf9 cells.…”
Section: Discussionmentioning
confidence: 97%
“…It also indicates that VSRs in insect cells share characteristics similar to those found in plant or animal cells, such as the P19 protein’s ability to bind with newly formed 21 nt and 22 nt RNA in plant cells, thereby hindering RISC assembly [ 26 , 44 ]. This regulatory mechanism is not limited to single-stranded RNA viruses but is also observed with FHV-B2 protein, NS1 protein of influenza A virus, Tomato aspermy virus (TAV)-2b protein, and other similar proteins [ 45 , 46 , 47 ]. Despite changes in gene regulation, there was no significant alteration observed within 24 h regarding the rate of apoptosis in Sf9 cells.…”
Section: Discussionmentioning
confidence: 97%
“… 293T cells. A/PR/8/34 (H1N1), A/WSN/33 (H1N1) [ 47 ] 2023 Mutations in the NS1 alter its function in regulating RIG-I-like receptor-mediated antiviral responses. 293T, A549, and MDCK cells.…”
Section: The Functions Of the Iav Ns1mentioning
confidence: 99%
“…Several studies including ours have now found that vsiRNAs were produced using VSR‐deficient mutant viruses (e.g. B2‐deficient mutant of NoV, NS1‐deficient mutant of IAV, 3A‐deficient mutant of HEV71 and NS2A‐deficient mutant of DENV2) in mammalian cells or suckling mice [19–21,24,25,30,34,57] as well as using wild‐type viruses [e.g. encephalomyocarditis virus (EMCV), ZIKV, Sindbis virus (SINV) and NoV] in undifferentiated cells or somatic cells [22,26–29].…”
Section: Putative Explanations About Why Vsirnas Were Not Detected St...mentioning
confidence: 99%